IMPLEMENTASI MANAJEMEN SUMBERDAYA TENAGA KEPENDIDIKAN DALAM MENINGKATKAN KUALITAS LAYANAN PENDIDIKAN AGAMA ISLAM SISWA - Syafrizal (UNISAN JURNAL, 2024)
Implementing the management of educational personnel resources properly will be able to improve the quality of Islamic religious education services, but the results of the author’s initial research at SMPN1 Kota Agung Barat Kabupaten Tanggamus, the management of educational personnel resources has been implemented but the quality of Islamic religious education services is still not good. increase. For this reason, the author tries to examine "Implementation of Educational Personnel Resource Management in Improving the Quality of Islamic Religious Education Services at SMPN1 Kota Agung Barat Kabupaten Tanggamus , East Lampung, Academic Year 2021/2022". The formulation of the main problem is how the implementation of educational staff resource management in improving the quality of Islamic religious education services, so that the purpose of the research is to determine the implementation of educational staff resource management in improving the quality of Islamic Religious Education services at SMPN1 Kota Agung Barat Kabupaten Tanggamus East Lampung The research method used is qualitative, with data sources: madrasa heads, Islamic Religious Education teachers and students. Data collection techniques: participatory observation, interviews and documentation. After the data is collected, then data reduction, data presentation, and data verification are carried out. The results of this study are: Implementation of educational staff resource management in increasing the effectiveness of Islamic Religious Education learning at SMPN1 Kota Agung Barat Kabupaten Tanggamus , namely the management of educational staff resources has been implemented both at the planning, coaching and development stages, assessment and compensation. Implementation of education staff resource management such as: planning teachers who teach according to their educational background, at least S.1, skilled in using learning methods and media, developing teacher competencies by involving teachers in upgrading and seminars, motivation to continue education, giving awards for outstanding teachers and sanctions for teachers who lack discipline and poor performance, involve teachers in every madrasa development, accept and develop the ideas and potential of teachers, carry out direct supervision activities on the activities of their teachers, the results of teacher performance assessments are immediately followed up, give rewards and attention to honorary teachers. The conclusion of the study: the implementation of educational staff resource management can improve the quality of Islamic religious education services for students at SMPN1 Kota Agung Barat Kabupaten Tanggamus , East Lampung.